Mathematical Model for a Radar Signal Reflected from Drone Propellers as Applied to the Method of Inverse Synthetic Aperture Radar in Bistatic Radar - E. C. Plotnitskaya; S. R. Heister; V. I. Veremyev (Известия высших учебных заведений России: Радиоэлектроника, 2023)
Introduction. The distinction of targets located in the same spatial resolution cell of a radar system includes the determination of the number of targets and their recognition. Recognition and distinction are directly related to the analysis of radar profiles (spectral, range, azimuth, etc.). Radar images of rotating drone elements obtained with the method of inverse synthetic aperture radar (ISAR) present particular interest. Such profiles are highly informative in terms of defining the drone design characteristics. When developing algorithms for constructing radar profiles of drone propellers based on ISAR, it is necessary to have a clear understanding of the movements of various points on the propeller blade surfaces. This understanding can be achieved by constructing a mathematical model for a signal reflected from drone propellers.Aim. To develop a mathematical model for a signal reflected from drone propellers in application to the method of ISAR in bistatic radar.Materials and methods. In the model under consideration, the propeller blade is represented by a set of point reflectors located along two lines passing through the front and rear edges of the blade. When developing the reflected signal model, variation in the phase structure of the reflected signal arising due to the translational motion of the drone and the rotation of its propeller blades, as well as their offset in space.Results. A mathematical model for a signal reflected from drone propellers in application to the method of ISAR in bistatic radar was developed. Signals reflected from one propeller blade, from one propeller, and from a set of drone propellers were simulated. The temporal and spectral structures of the reflected signals for two variants of blade representation were analyzed.Conclusion. The developed mathematical model can be used when developing an algorithm for constructing images of drone propellers by the method of inverse synthetic aperture radar in a bistatic radar system.